PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KOMITMEN ORGANISASI MELALUI MOTIVASI - NUR IMANNI, RITFY (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:PT Asuransi Jiwa Manulife Indonesia is a company engaged in the field of life insurance. Quality of work life depends on how the company is able to provide good working conditions for employees, so employees have a sense of security and comfort during work.The purpose of this study was to analyze the influence of the quality of work life on organizational commitment. As well as the improvement of the mediating role of motivation to influence the quality of work life on organizational commitment. Samples were 36 peoples at the branch synergies. The data analysis technique used is Structural Equation Model Partial Least Square.The results of the study explainedthe quality of work life have significant positive effect on organizational commitment and motivation. Motivation positive have significant effect on organizational commitment. Motivation is not mediate the effect of the quality of working life on organizational commitment. Keywords:quality of work life, organizational commitment, and motivation.